1974
DOI: 10.1029/ja079i025p03665
|View full text |Cite
|
Sign up to set email alerts
|

Background Starlight observed from Pioneer 10

Abstract: After passage through the asteroid belt the Pioneer 10 imaging photopolarimeter observed integrated starlight and diffuse galactic light for the first time in the absence of zodiacal light. Brightnesses in the blue are presented with and without individually resolved stars for regions of the sky observed when Pioneer 10 was 4.64 AU from the sun. The Pioneer 10 and 11 asteroid-Jupiter probes have provided the first opportunity to determine the spatial distribution of interplanetary dust beyond I AU and to map t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…The spacecraft trajectory and observing geometry at four spacecraft positions in the asteroid belt are shown schematically in Figure 2 magnitude were prepared by the method described by Weinberg et al [1974]. The difference in intercept between these two days agreed within 1% with the change in sensitivity of 11.5% given by the five bright stars.…”
Section: Instrument Operation and Calibration mentioning
confidence: 92%
See 2 more Smart Citations
“…The spacecraft trajectory and observing geometry at four spacecraft positions in the asteroid belt are shown schematically in Figure 2 magnitude were prepared by the method described by Weinberg et al [1974]. The difference in intercept between these two days agreed within 1% with the change in sensitivity of 11.5% given by the five bright stars.…”
Section: Instrument Operation and Calibration mentioning
confidence: 92%
“…The IPP measures orthogonal brightness components in blue (3900-5000 A) and red (5950-7200 A) light to provide sky brightness, color, and polarization information [Pellicori et al, 1973;Weinberg et al, 1974]. A complete data cycle consists of ten spacecraft rolls, one each for dark current and calibration measurements and eight for sky measurements with a 2.3 ø by 2.3 ø field of view.…”
Section: Instrument Operation and Calibration mentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed description of the observations and the primary data processing can be found in, e.g., Weinberg et al (1974) and Gordon et al (1998). Using the Pioneer 10 IPP data collected at various heliocentric distances R, Hanner et al (1974) find that the ZL brightness is below the detectable level of the instrument when the spacecraft is at beyond R = 3.26 AU.…”
Section: Observations and Reductionsmentioning
confidence: 99%
“…A detailed description of the observations and of the primary data processing can be found in, e.g., Weinberg et al (1974) and Gordon et al (1998). Using the Pioneer 10 IPP data collected at various heliocentric distances R, Hanner et al (1974) found that the ZL brightness is below the detectable level of the instrument when the spacecraft was at beyond R = 3.26 AU.…”
Section: Observations and Reductionsmentioning
confidence: 99%